Neuropathologic and molecular aspects of a canine distemper epizootic in red foxes in Germany - Franziska Geiselhardt; Martin Peters; Sven Kleinschmidt; Elisa Chludzinski; Melanie Stoff; Martin Ludlow; Andreas Beineke (Scientific Reports, 2022)
Abstract In the last fifteen years, an epidemic of canine distemper virus (CDV) with marked neurotropism has occurred in Europe after a longer period of endemic transmission. Many wildlife species have been infected, with red foxes (Vulpes vulpes) being particularly affected. Given that this species is assumed to mediate cross-species CDV infections to domestic and wild animals, tissue samples from foxes with confirmed CDV infection in North-Western Germany were investigated to better understand the neurotropic aspects of the disease. This analysis included histopathology, virus distribution and cell tropism, phenotyping of inflammatory responses and determination of the genotype of the viruses based on the phylogeny of the hemagglutinin (H) gene. The predominant lesion type is gliosis in both gray and white matter areas associated with an accumulation of Iba1+ macrophages/microglia and upregulation of major histocompatibility complex class II molecules in the brain, while sequestration of CD3+ T and Pax5+ B cell in CDV-infected foxes is limited. Demyelination is found in few foxes, characterized by reduced myelin staining with loss of CNPase+ oligodendrocytes in the cerebellar white matter and brainstem. In addition, axonal damage, characterized by β-amyloid precursor protein expression, is found mainly in these brain regions. In situ hybridization reveals a primary infection of the cerebral and cerebellar gray matter and brain stem. Iba1+ cells and NeuN+ neurons represent the main CDV targets. Sequencing of the CDV H open reading frame from fox tissues reveals that the virus strains belongs to three different sub-lineages of the Europe-1/South America-1 genotype, suggesting independent transmission lines.